Reflexões sobre a revitalização de um laboratório de ciências : materiais didáticos e roteiros práticos - Medeiros, Olma Karoline Cruz de (2018)
The science labs are part of the school history, their use has relevance in the teaching and learning process, sometimes they are part of the students' daily life or they have sterile participation in the educational process. In this context, this work investigated the revitalization of a science laboratory at a school in the city of Catalão - GO, which for many years was unused, trying to incorporate the use of a space more suitable for practical activities. In addition, didactic materials and scripts based on the knowledge and teaching experience were elaborated with proposals of works that could be used by the faculty of the school and others, trying to contribute with the teaching of Sciences and Biology. Data were collected on the functions of didactic materials, practical activities, use of the science laboratory and the scripts. The research referred mainly to the assumptions of Vygotsky's sociocultural theory in relation to practical activities, as well as other actors. The research was characterized by being qualitative, using the narrative methodology, describing the revitalization process, interactions, implications and subjectivities, with records of activities in logbook and recorded interviews. The results point to the professional fragility of public education, the lack of collaboration between teachers and the implications of attempts to put into practice the development of a formal space for teaching, as well as difficulties in the organization of a material with an investigative approach for teacher's work aid